Application of deconvolutional treatment to powder diffraction data collected with a Bragg-Brentano diffractometer with a contaminated Cu target and a Ni filter. Issue 3 (September 2020) - Ida, Takashi
Abstract : A deconvolutional method for preprocessing powder diffraction data has been improved. The cumulants of instrumental aberration functions of Bragg-Brentano (Parrish) diffractometer calculated up to the fourth order are presented. The treatments of axial-divergence aberration and the effective spectroscopic profile of the source X-ray have been simplified from those used in previous methods. The current method has been applied to powder diffraction data collected with a Cu-target X-ray tube, used over 20 years, and a Ni-foil K β filter.